Growth of Rhizophora apiculata and Rhizophora mucronata on Different Sediment Types in the Marine Station Area of the Universitas Riau, Dumai - Prameswari, Cinta Riyanda; Efriyeldi, Efriyeldi; Siregar, Yusni Ikhwan; Zulkifli, Zulkifli; Ilahi, Ilham (Journal of Coastal and Ocean Sciences, 2026)
Mangroves play an important role in maintaining coastal stability and supporting ecological functions in coastal waters. This study aimed to analyze differences in the growth of Rhizophora apiculata and R. mucronata under different sediment types at the Marine Station of Universitas Riau, Dumai. Observations were conducted for 10 weeks at two stations, namely sandy mud and mud sediments, using 24 mangrove seedlings with an initial height of ≥ 60 cm. The results showed significant differences in growth between mangrove species and between observation stations (p < 0.05). In sandy mud sediment, R. apiculata exhibited better growth (64.33 ± 3.92 mm; 7.20 ± 0.46 mm), whereas in mud sediment, R. mucronata showed more optimal growth (72.36 ± 7.54 mm; 7.87 ± 0.52 mm). Seedling survival reached 100% at both stations. These findings indicate that the suitability of mangrove species to sediment characteristics is an important consideration in mangrove rehabilitation efforts